Aspergillus terreus Inhibits Growth and Induces Morphological Abnormalities in Pythium aphanidermatum and Suppresses Pythium-Induced Damping-Off of Cucumber - Halo, Boshra A.; Al-Yahyai, Rashid A.; Al-Sadi, Abdullah M. (Frontiers in Microbiology, 2018)
The study investigated the efficacy of two isolates of Aspergillus terreus (65P and 9F) on the growth, morphology and pathogenicity of Pythium aphanidermatum on cucumber. In vitro tests showed that the two isolates inhibited the growth of P. aphanidermatum in culture. Investigating P. aphanidermatum hyphae close to the inhibition zone showed that the hyphae showed abnormal growth and loss of internal content. Treating P. aphanidermatum with the culture filtrate of A. terreus resulted in significant rise in cellular leakage of P. aphanidermatum mycelium. Testing glucanase enzyme activity by both A. terreus isolates showed a significant increase in glucanase activity. This suggests that the cell walls of Pythium, which consist of glucan, are affected by the glucanase enzyme produced by A. terreus. In addition, Aspergillus isolates produced siderephore, which is suggested to be involved in inhibition of Pythium growth. Also, the culture filtrates of 65P and 9F isolates significantly reduced spore production by P. aphanidermatum compared to the control (P < 0.05). In bioassay tests, the two isolates of A. terreus increased the survival rate of cucumber seedlings from 10-20% in the control seedlings treated with P. aphanidermatum to 38-39% when the biocontrol agents were used. No disease symptoms were observed on cucumber seedlings only treated with the isolates 65P and 9F of A. terreus. In addition, the A. terreus isolates did not have any negative effects on the growth of cucumber seedlings. This study shows that isolates of A. terreus can help suppress Pythium-induced damping-off of cucumber, which is suggested to be through the effect of A. terreus and its glucanase enzyme on P. aphanidermatum mycelium.